Pyelonephritis during pregnancy: A cause for an acquired deficiency of protein Z - Nien, Jyh Kae (2008)
OBJECTIVE: Pyelonephritis has a more severe course during pregnancy than in the non-pregnant state. This has been attributed to the increased susceptibility of pregnant women to microbial products. An acquired protein Z deficiency has been reported when there is excessive thrombin activity. The aim of this study was to determine whether pyelonephritis during pregnancy is associated with changes in maternal plasma protein Z concentrations. STUDY DESIGN: A cross-sectional study was conducted to compare plasma protein Z concentrations between normal pregnant women (n=71) and pregnant women with pyelonephritis (n=42). Protein Z concentrations were measured by ELISA. Parametric and non-parametric statistics were used for analysis. RESULTS: Patients with pyelonephritis had a significantly lower median plasma concentration of protein Z than did patients with normal pregnancies [median 2.14 μg/mL (0.4-3.4) vs. median 2.36 μg/mL (1.09-3.36); p=0.03]. There was no difference in the median plasma concentration of anti-protein Z antibodies between patients with pyelonephritis and those with normal pregnancies. CONCLUSION: The median maternal plasma protein Z concentration was significantly lower in patients with pyelonephritis during pregnancy than in patients with normal pregnancies.